How can LS Improve the Effectiveness of PBL-TaRL in Biology Learning with Ecosystem Material? - Septiana, Bella; Misri Supadmi; Sumani; Marheny Lukitasari (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
The main objective of this research is to analyze the effectiveness of PBL-TaRL implementation through Lesson Study (LS) on Ecosystem material in high school. The research design used a combination of qualitative and quantitative data through mixed methods with triangulation. The study consisted of three cycles that observed students' learning activities especially in the Plan, Do, and See stages. A pretest-posttest sheet in the form of a google form and an observation sheet were used as instruments in this study. All data were analyzed qualitatively with paired sample t-test and N-Gain test. The results showed that LS-based PBL-TaRL had effective results in learning, from the acquisition of N-Gain in cycle 1 of 72.2%, 95.75% in cycle 2, and 89.66% in cycle 3. These findings are expected to provide information for subject teachers, and the government in the field of education to further develop and apply the PBL-TaRL approach.